Classification, diagnosis and clinical strategy of congenital coronary artery disease in children - Feng, Juan; Zhao, Jingshu; Li, Jun; Sun, Zhenyun; Li, Qiao (Frontiers in Pediatrics, 2023)
Some of the congenital coronary artery diseases in children have potential life-threatening complications. In addition to anatomical classification, the peadiatricians should pay more attention to the risk of adverse cardiac events classification; and then, they can eventrually make the personalized guidance suggestions and treatment decisions according to different diseases